Radio wars in PNG: NauFM's tough struggle - Raphael Semel (Asia Pacific Network, 1996)
While NauFM goes from strength-to-strength, its establishment rival Radio Kalang has been on the verge of collapse. However, clouding NauFM's silver lining are serious questions about the quality and style of its news and information programs.